Factors influencing back pain treatment behaviour change. Issue 5 (14th September 2015) - McClymont, Hoda; Gow, Jeff; Hume, Margee; Perry, Chad
Abstract : Purpose: – The authors seek to better understand the critical incidents and factors that influence the switching behaviours of back pain sufferers who use mainstream and/or complementary and alternative medicine (Edvardsson, 1998). That is, the purpose of this paper is to uncover how they switch between treatments and treatment providers; in particular, this research investigates two issues: the triggers of their switching and their switching paths, and how their emotions are involved in that switching. The contribution is the first empirical foundation for an understanding of these two issues in the context of back pain. Design/methodology/approach: – The qualitative technique of convergent interviewing was used. It involved conducting a series of long, initially rather unstructured interviews to converge on the important topic areas to the back pain sufferers and why they engage in their treatment behaviour. Findings: – This study investigated the triggers and categories of triggers that impact upon switching behaviours between bio-medical and CAT healthcare. Four main areas of findings were identified. First, although the literature identified four categories of triggers for switching, namely, situational, reactional, influential and personal characteristics, the findings of this research confirmed only two of these: reactional and situational triggers. The influential category of triggers was found to be more of a moderating factor between switching triggers and switching behaviours rather than a trigger factor on its own. Further, no evidence came to light that could confirm or disconfirm the roles of personal characteristics on switching behaviour and so this issue remains unresolved. Research limitations/implications: – The methodology used in this research was an exploratory one and so the findings must be used with caution. Further research, using a more quantitative methodology, is warranted to confirm the findings of this research. Also, this research focused on a subset of switching issues and so might not provide a holistic framework. Future investigations should therefore consider and clarify the role of emotion, time and voice in the switching model devised from this study. Originality/value: – This paper provides new evidence on the reasons for back pain sufferers consuming different treatment modes and the reasons for their switching and includes an exploratory investigation of the role of emotions in this decision making.